Tecnologias de produção e de controle de qualidade da matéria-prima vegetal, obtida a partir das folhas de angico (Anadenanthera colubrina (Vell) Brenan var. cebil (Griseb.) Altschul) - Souza, Valmir Gomes de (2018)
Anadenanthera colubrina (angico) is a medicinal plant, native to caatinga, whose extractive solutions are popularly used to treat infections and inflammations of diseases of the gastric and respiratory tract, being one of the ten medicinal plants, most used in Northeast Brazil. Researchers, evaluating phytochemical studies of extracts of A. colubrina demonstrated the presence of secondary metabolites, such as: alkaloids, steroids, triterpenoids, phenolic compounds and flavonoids such as quercetin, thus the purpose of this work was to propose the validation and covalidation of analytical method for analysis of quercetin by CLAE-DAD, standardization of A. colubrina plant extract (fluid extract, dry extract), optimization of the drying conditions of the extract by spray drying and pre-formulated production with different technological adjuvants and study of their accelerated stability. The validation of the analytical method followed protocols of RDC 899/2003 (ANVISA). The standardization of the fluid extract of the leaves of A. colubrina evaluated the influence of the alcoholic content and the particle size of the vegetal drug in the extractive process, being the extractive efficiency determined as a function of the concentration of the quercetin marker, analyzed by HPLCDAD. The standardization of the nebulized dry extract (ESN) evaluated the influence of air inlet temperature, pump feed flow and adjuvant ratio through factorial design 23 + 1 using as answer the quercetin marker content and process yield. The pre-formulations were produced by physical mixing 1:1, containing dried nebulized extract (ESN) and pregelatinized starch, microcrystalline cellulose 102, maltodextrin and lactose M 200, and then accelerated stability study for 180 days according to official guide (RDC 45/2012). The results demonstrate that the extractive efficiency occurs at the conditions of solvent proportion at 50 and 70% ethanol with quercetin concentration of 122.5 and 124.2 μg / mL respectively. The evaluation of particle sizes in the extractive process has shown that as particle size is reduced, there is an increase in the extractive efficiency of flavonoid quercetin under the conditions evaluated. The analytical method validated by CLAE-DAD demonstrated that the method is specific, linear, sensitive, accurate, excellent recovery, robust and suitable for the intended purpose, according to official guides. The factorial design applied to the production of the dried extract of A. colubrina indicated the optimum drying condition, such as 10% adjuvant ratio, 160ºC inlet temperature and 8mL / min pump flow. The results of the accelerated stability study of A. colubrina pre-formulated dry extract showed that the pre-formulated were stable and follow the zero-order kinetic model of degradation. The study determined the time required for the quercetin content to degrade by 10% in relation to the initial content, and the following times were obtained in decreasing order of stability: starch> microcrystalline cellulose> maltodextrin> lactose and the pre-formulated starch (41 months) and cellulose (15 months) the ones that had better performance. The results obtained in the present study allowed to add new technologies in the production and quality control of products derived from A. colubrina, producing dry extract standardized by spray-drying, with maintenance of the characteristics of its quality.